2016
DOI: 10.1002/cne.24052
|View full text |Cite
|
Sign up to set email alerts
|

Claustral afferents of superior parietal areas PEc and PE in the macaque

Abstract: The exposed surface of the primate superior parietal cortex includes two cytoarchitectonically defined areas, the PEc and PE. In the present study we describe the distribution of neurons projecting from the claustrum to these areas. Retrograde neuronal tracers were injected by direct visualization of regions of interest, and the location of injection sites was reconstructed relative to cytoarchitectural borders. For comparison, the patterns of claustral label that resulted from injections involving neighboring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 52 publications
(99 reference statements)
3
21
0
Order By: Relevance
“…Regionalization of CLA connections is also evident following tracer injections in prefrontal (Burman et al, 2011;Reser et al, 2014Reser et al, , 2017Selemon & Goldman-Rakic, 1988), inferior temporal (Baizer et al, 1993), posterior parietal (Baizer et al, 1993;Gamberini et al, 2017;Selemon & Goldman-Rakic, 1988), and orbitofrontal cortex (Morecraft, Geula, & Mesulam, 1992; also shown by fiber degeneration staining, Leichnetz & Astruc, 1975). Finally, there has been a long-standing assertion that the En components of the CLA complex project selectively to the "limbic" areas of cortex, especially the orbitofrontal, ventromedial prefrontal, and anterior cingulate areas, while the insular CLA projects more to higherorder sensory and association areas.…”
Section: Delineating Cla and En In Primates By Anatomical Connectivmentioning
confidence: 92%
See 4 more Smart Citations
“…Regionalization of CLA connections is also evident following tracer injections in prefrontal (Burman et al, 2011;Reser et al, 2014Reser et al, , 2017Selemon & Goldman-Rakic, 1988), inferior temporal (Baizer et al, 1993), posterior parietal (Baizer et al, 1993;Gamberini et al, 2017;Selemon & Goldman-Rakic, 1988), and orbitofrontal cortex (Morecraft, Geula, & Mesulam, 1992; also shown by fiber degeneration staining, Leichnetz & Astruc, 1975). Finally, there has been a long-standing assertion that the En components of the CLA complex project selectively to the "limbic" areas of cortex, especially the orbitofrontal, ventromedial prefrontal, and anterior cingulate areas, while the insular CLA projects more to higherorder sensory and association areas.…”
Section: Delineating Cla and En In Primates By Anatomical Connectivmentioning
confidence: 92%
“…Additional work has shown that there are some modality‐specific characteristics of CLA connectivity, including localization of visual connections to the ventral and caudal aspects of the CLA, with somatomotor projections concentrated in the dorsal regions (Baizer et al, ; Pearson et al, ). Regionalization of CLA connections is also evident following tracer injections in prefrontal (Burman et al, ; Reser et al, , ; Selemon & Goldman‐Rakic, ), inferior temporal (Baizer et al, ), posterior parietal (Baizer et al, ; Gamberini et al, ; Selemon & Goldman‐Rakic, ), and orbitofrontal cortex (Morecraft, Geula, & Mesulam, ; also shown by fiber degeneration staining, Leichnetz & Astruc, ). Finally, there has been a long‐standing assertion that the En components of the CLA complex project selectively to the “limbic” areas of cortex, especially the orbitofrontal, ventromedial prefrontal, and anterior cingulate areas, while the insular CLA projects more to higher‐order sensory and association areas.…”
Section: Reassessing the Identity Of The Cla And En In Anthropoid Primentioning
confidence: 94%
See 3 more Smart Citations